Similitudes: olhares sobre um processo de criação em dança na E.E.E. Luiz Nunes Direito, em Ananindeua-PA - CUNHA, Antonio Luis Monteiro da (2018)
This work promotes reflections from the construction process in the choreographic language of contemporary dance show called Similarities in the public school LuizNunes Law in Anantapur, exposing the importance of dance in the school environment.Therefore, highlighting the contributions in making art education from my experience as a student, dancer and, consequently, choreographer, promoting a collective findings do with the individuals involved from the theme generator. However, analyzing the free flow of ideas to include everyone in the process.In this research shows is critical and reflective dialogue with the subjects' with my eyes, linking up with the authors, resulting in a relationship between dance, body and education.